Our experience of percutaneous ventricular septal defects closure - N. Yashchuk; I. Ditkivskyy; B. Cherpak; O. Mazur; V. Beshliaga; V. Lazoryshynetz (Ukrainian Journal of Cardiovascular Surgery, 2017)
We are presenting our experience of percutaneous VSD closure and thereafter we will try to assess the efficacy and safety of the procedure.Materials and methods. 52 patients had percutaneous VSD closure in period from August 2012 to February 2017 in Amosov National Institute of cardiovascular surgery. Of them 49 pts (94%) had congenital heart defect, 2 pts (3,8%) had residual shunt after surgery and one patient (1,2%) had posttraumatic defect. Two pts had hybrid VSD closure. 17 defects were muscular (32,7%), 35 pts. had perimembranous VSD (68,3%). Mean age of the patients was 15,86±16,37 years.Results. The rate of success was 94,2% (49pts). Major complications had two pts (3,8%). Of them one patient had sig-nificant hemolysis requiring conversion to surgery and second patient had tricuspid valve chordae detachment with severe tricuspid regurgitation. Two patients had low grade transitional conduction disturbances; one of them needed temporary pacemaker wire placement for a couple of days after procedure. These two patients had complete conduction recovery. Mean follow-up period was 29,4±17,3 months.Conclusion. Percutaneous VSD closure is safe and effective procedure. The rate of complications is not higher than after cardiac surgery. More experience, longer follow-up, multicenter randomized placebo controlled investigations are warranted.